A study of polymorphic endogenous retroviruses in humans: Implications in host health and genome evolution. - Wildschutte, Julia. (2017)
Abstract: Human endogenous retroviruses (HERVs) result from the integration of retroviral DNA into germline cells. The recently active human MMTV-like HML-2 group has been the focus of this project. An analysis of the HML-2 group reveals their representation in the published genome by ~90 full-length proviruses and ~1000 solitary-LTRs. The HML- 2 proviruses can be divided into three subgroups, based on the phylogenetic comparison of the paired LTRs belonging to each element, namely, the LTR5Hs, LTR5A, and LTR5B. The analyses provide sequence-based and phylogenetic support that the LTR5B are the oldest of the HML-2 proviruses, with a few shared sites in Old World monkeys. Also supported by phylogenetic analysis and by estimated times of the activities of each subgroup, the LTR5B subgroup is ancestral to both the LTR5A and LTR5-Hs. Only the LTR5-Hs have been active in humans. Phylogenetic analyses indicate the evolutionary activities of the LTR5-Hs have differed from that of the LTR5A and B subgroups, the latter two having experienced increases in copy number as a direct result of association with segmental duplication events within the host genome. Also we present the findings that the LTR5A elements are associated with a specific group of genome segments, and are found in more than half of the recently formed duplicons. The HML-2 group represents the only HERVs with human-specific integrations, of which at least 11 HML-2 proviruses are polymorphic in integration site and frequency within the population. The expression of HML-2 proviruses has been well reported to be up-regulated in a number of diseases. The effects of HERV expression in human tissues are poorly understood, as is how HML-2 expression relates to a particular diseased state. In this respect, polymorphic integrations have been given attention as they are conserved in sequence though present in a fraction of the population. We used high resolution DNA hybridization from human genomic DNAs in order to visually infer the distribution of newly formed and as-yet uncharacterized polymorphic HML-2 proviruses. The case-control analyses of DNAs from two human diseases revealed no statistical support for a genetic association of any `new' polymorphic element with disease, and are consistent with previous studies of similar approach. Nevertheless, we have provided evidence that as many as 15 polymorphic proviruses are detected within human DNAs that vary in frequencies among the samples. We observed a few present at quite low frequencies, for example in one or two of 120 tested samples -below 1%, with regard to the samples analyzed, a far lower representation than seen in any other polymorphic provirus. Such a provirus would be highly conserved and might also exhibit retained functions.; Thesis (Ph.D.)--Tufts University, 2011.; Submitted to the Dept. of Molecular Microbiology.; Advisor: John Coffin.; Committee: Carol Kumamoto, Katya Heldwein, Naomi Rosenberg, and Paul Bieniasz.; Keywords: Molecular biology, and Microbiology.